The Effectiveness of Prompt Engineering in Islamic Education: Analyzing AI as a Cognitive Partner to Enhance Digital Literacy - Fuady, Ahmad Silmul; Wahyuni , Maulida; Amaliyah, Khoiriyatul; Rusydah, Arini; AM, Ratna Puspita (Journal of Educational Management Research, 2025)
This study aims to examine the role of prompt engineering in fostering digital literacy and reflective theological inquiry within Islamic education by positioning AI as a cognitive partner rather than a passive tool. Employing a qualitative literature study design, the research analysed scholarly sources using an interactive framework consisting of data condensation, data display, and conclusion drawing. The findings indicate that structured prompting strategies, including Zero-shot, Few-shot, and Chain-of-Thought approaches, enhance students’ interpretive reasoning, ethical verification, and dialogical engagement, aligning with the principles of Tafakkur and Tabayyun. Prompt engineering functions as intellectual scaffolding, transforming AI interactions into reflective inquiry and promoting higher-order thinking skills in religious learning contexts. These results suggest that AI-assisted learning, guided by thoughtful prompting, supports the cultivation of Ijtihad Digital, ethical discernment, and responsible human-AI collaboration. The study highlights the pedagogical potential of integrating AI through prompt engineering to advance contemporary Islamic education practices, reinforcing critical thinking and digital competence.